Genetic and morphological aspects of the enterocutaneous fistula development - Yu. Usenko; Ya. Yu. Voitiv (Клінічна хірургія)
Objective. To analyze the frequency of polymorphic variants of matrix metalloproteinase-2 (C-1306 → T) and tissue inhibitors of metalloproteinase-2 (G303 → A) genes in patients with enterocutaneous fistulas and to identify the connection with morphological changes of connective tissue.